Developing a charter of spiritual care for patients. (26th December 2020) - Heidari, Akram; Kazemi, Abdolhasan; Abbasi, Mohammad; Adeli, Seyed hasan; Ahmari tehran, Hoda; Eskandari, Narges; Heidari, Morteza; Khalajinia, Zohre; Yoosefee, Sadegh
Abstract: Background: Spirituality is recognized as an important issue in health care, and every individual has spiritual needs. Despite increased knowledge about spiritual care and its necessity, there is no unique agreed-upon framework for spiritual care among the practitioners. This study aimed to explore the concept from the viewpoint of both health-care providers and patients within the Iranian social, cultural and overall contexts and present a charter for providing spiritual care. Methods: The first phase of the study was a systematic literature review. The next phase consisted of two qualitative studies on the components of spiritual care from the perspective of healthcare providers and its dimensions as perceived by patients. The findings were then integrated to make up a charter draft that was accredited through expert opinion. Results: The review of literatures led to the identification of two main themes and 10 themes. Perspectives of health-care providers were categorized into four main themes and 10 themes, and patients' opinions were classified into three main themes and 11 themes. The themes and their subthemes were integrated to build the concepts and form the proposed charter with 30 statements. Conclusion: The charter of spiritual care for patients is intended to present an agreed-upon framework for spiritual care delivery and resolve some of the problems in this path. This can improve health-care delivery system.